Visual semiotics of the Menak Lare manuscript Illumination for character education - Muhammad Ibnan Syarif; Dwi Budi Harto; Bangkit Sanjaya; Nur Fajrie (Institut Seni Indonesia Surakarta, 2026)
Studies on the Menak tradition have generally focused on philology, literary history, textual transmission, and heroic narratives. The illumination of Serat Menak Lare, however, has rarely been read as a visual system that carries cultural meanings and educational values. This research applies a qualitative interpretive approach, using the Serat Menak Laremanuscript from the Sonobudoyo Museum Yogyakarta collection, coded B55_00152, as its object of study. Among the nine illuminations found in the manuscript, the analysis focuses on pages 289–290, since they form the most complex and representative double page illumination. Data were collected through visual observation and library research. The analysis was conducted through visual description, semiotic classification of icons, indexes, and symbols, interpretation within Javanese-Islamic cultural contexts, and mapping of character education values. Research credibility was strengthened through triangulation of sources, methods, and theory. The findings show that the illumination is organized through symmetrical composition, layered frames, visual hierarchy, motif repetition, and color arrangement. The motifs of kala, crowned elephants carrying maces, padma, floral vines, and gateway-like forms construct a visual narrative of protection, moral authority, purity, and cultural continuity. Pragmatically, the illumination does not function as a literal illustration of the Amir Hamzah story. It works instead as a visual threshold that guides readers into the moral and religious atmosphere of the text. This study offers a framework for reading Javanese-Islamic manuscript illumination as visual heritage and as a source of reflection for character education.